Նոր առաներենի (Կովկասի թաթերենի) ուսումնասիրության պատմությունից - Տորք Դալալյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Арраноязычные этнографические группы никогда не имели общего самоназвания, следовательно их маркирование под названием татлишь условно принято в современной науке. Учитывая эти факты, а так же пейоративное происхождение термина тат, в статье предлагается новый научный термин для языка - новоарранский, и для его трех вариантов - мусульмано-арранский, армяно-арранский,еврейско-арранский. Arranian-speaking ethnographical groups have never had a general autonym hence their definition as Tats is only conditionally accepted by modern researchers. Taking into consideration these facts, as well as the pejorative origin of the term Tat, we offer in our paper a new scientific term for this language - Modern Arranian, and for its three variants - Muslim Arranian, Armeno-Aranian and Judeo-Arranian.
Keywords: Language and Literature